Fanconi Anemia Type C: Results of Population Carrier Testing [2A]. (May 2018) - Bardos, Jonah D.; Terhaar, Catherine; Echeverri, Natalia; Longman, Ryan
Abstract : INTRODUCTION: Fanconi Anemia Type C (FAC) is an autosomal recessive disorder characterized by skeletal malformations, bone marrow failure, increased risk of malignancy, and severe aplastic anemia. Currently, carrier testing for FAC is recommended for the Ashkenazi Jewish (AJ) population. A joint ACOG/ACMG statement highlighted the increasingly multi-ethnic society as consideration for pan-ethnic carrier testing, and recent ACOG committee opinion states that pan-ethnic testing is a reasonable strategy. Our current study assesses how many non-AJ individuals screened positive for FAC when pan-ethnic carrier testing was implemented. METHODS: Retrospective database analysis of individuals that received expanded carrier testing utilizing a genotyping panel for three pathologic variants of FAC (c.322delG, IVS4 c.456(+4)A>T, p.R548X) was performed. Expected number of positive carriers in AJ and non-AJ groups were calculated and compared to observed rates. Chi-square analysis was performed to assess for statistical significance (p < 0.01). RESULTS: A total of 71, 235 individuals were tested for FAC. A higher than expected number of non-AJ individuals tested positive for FAC (56 observed vs 8.89 expected, p<0.001). The number of AJ individuals that screened positive was consistent with expected values (10 observed vs 11.11 expected, p<0.73). CONCLUSION: Non-AJ carriers of FAC were more common than expected in this cohort. Pan-ethnic expanded carrier testing will increase the detection of carriers for FAC compared with current ethnicity based screening recommendations. Importantly, carriers of FAC who would be missed by ethnicity based testing convention, will be identified allowing for more complete genetic counseling and family planning options for those who choose testing.